Study and Investigation of High Strength Concrete using Fly Ash, and Ground Granulated Blast Furnace with Various Materials - Linganna, Prudhvi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Concrete is generally classified as Normal strength concrete, high strength concrete and ultrahigh strength concrete. High strength label was adopted to concrete having strength 50Mpa and above. In particular construction of high-rise buildings and long span bridges, concrete strengths of 90 to 120Mpa are occasionally used. High performance concrete is used for concrete mixture which posses high workability, high strength, high modulus of elasticity, high density, high dimensional stability and resistance to chemical attack. A substantial reduction of quantity of mixing of water is the fundamental step for making HPC. Adopting W/C ratio in the range of 0.25 to 0.3 and getting high slump is possible only with the use of super plasticizer. The use of appropriate super plasticizer is a key material for making HPC. In this project the effects of fly ash, ground granulated blast furnace slag, in M-50 grade concrete with different material proportions are studied for compressive, split tensile and flexural strengths.With constant percentages of Fly Ash and different percentage of GGBS of 5%, 10% and 15% with 1% of super plasticizer are used then the compressive strength, flexure strength and split tensile strength values are decreased by increasing the GGBS%.